STATUS KONTROL ASMA DENGAN KUALITAS HIDUP PADA ANAK DENGAN ASMA BRONKIAL - Ni Luh Putu Kemala Putri; N.L.K Sulisnadewi; I NYOMAN RIBEK (Jurnal Gema Keperawatan, 2019)
The purpose of this study was to determine the relationship of asthma control status with quality of life in children with bronchial asthma in Klungkung Hospital in 2019. The study design used correlational analytic with aapproach cross sectional. The research sample was 68 people using non probability sampling, namely purposive sampling. Asthma control status was measured by Chilhood Asthma Control Test (C-ACT) and quality of life using Pediatric Quality of Life Inventory (PedsQL). The results showed that the average age of children was seven years, 57.4% were male. The average score of asthma control showed uncontrolled asthma (18.57) and quality of life scores showed impaired quality of life (69,13).statistical test results Pearson obtained p = 0,000 α (0,05), which means that the hypothesisisaccepted by calculating the value of r (rho). Results = 0.796 means that the control status of asthma has a strong relationship with quality of life, namely asthma sufferers who have no asthma controlled will tend to have a disrupted quality of life.